2018
DOI: 10.3390/v10050229
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pathogenesis of Asian and African-Lineage Zika Virus in Indian Rhesus Macaque’s and Development of a Non-Human Primate Model Suitable for the Evaluation of New Drugs and Vaccines

Abstract: The establishment of a well characterized non-human primate model of Zika virus (ZIKV) infection is critical for the development of medical interventions. In this study, challenging Indian rhesus macaques (IRMs) with ZIKV strains of the Asian lineage resulted in dose-dependent peak viral loads between days 2 and 5 post infection and a robust immune response which protected the animals from homologous and heterologous re-challenge. In contrast, viremia in IRMs challenged with an African lineage strain was below… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…Protection of animal models against heterologous challenge and cross-neutralization capabilities of antisera from multiple vaccine platforms 8,17,18,21 suggest that data from a single challenge strain may be sufficient to show cross protection against ZIKV strains from other lineages. Several groups have developed rhesus macaque challenge models using Zika strain PRVABC59 6,7,9,12,31 which is a well-documented and characterized isolate from human serum and is representative of viruses that were circulating in the Americas during the 2015-2016 outbreak 16 . We therefore selected PRVABC59 as the challenge strain for our studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protection of animal models against heterologous challenge and cross-neutralization capabilities of antisera from multiple vaccine platforms 8,17,18,21 suggest that data from a single challenge strain may be sufficient to show cross protection against ZIKV strains from other lineages. Several groups have developed rhesus macaque challenge models using Zika strain PRVABC59 6,7,9,12,31 which is a well-documented and characterized isolate from human serum and is representative of viruses that were circulating in the Americas during the 2015-2016 outbreak 16 . We therefore selected PRVABC59 as the challenge strain for our studies.…”
Section: Discussionmentioning
confidence: 99%
“…Results to date have supported neutralizing antibodies as an immune marker that is reasonably likely to predict clinical benefit of several ZIKV vaccines 4,5 . Indian rhesus macaques (Macaca mulatta) are susceptible to ZIKV infection and have been used extensively as a model to study efficacy of ZIKV vaccines and pathogenesis of multiple ZIKV isolates [6][7][8][9][10] . ZIKV infection can be performed by subcutaneous injection, which mimics infection via mosquito bite and causes consistent viremia [11][12][13][14][15] .…”
mentioning
confidence: 99%
“…Infection with ZIKV resulted in viremia that peaked around 2–6 days post-infection, followed by viral clearance. Importantly, viral RNA could be detected in various body fluids including urine, saliva, seminal fluid, vaginal secretions and cerebrospinal fluid, indicating similar dissemination patterns compared to humans [ 211 , 212 , 213 , 214 , 215 , 216 , 217 ]. Furthermore, mucosal viral inoculation (vaginal or rectal) was shown to lead to productive infection in macaques, mimicking the anogenital transmission route in humans [ 218 ].…”
Section: In Vivo Modelsmentioning
confidence: 99%
“…African ZIKV strains typically cause more productive and more lethal infections than Asian strains in cell culture [28][29][30][31][32][33][34] , they are more transmissible by mosquitoes [35][36][37][38][39] and they are associated with more severe pathology in adult mice and mouse embryos 34,[40][41][42][43][44][45][46][47][48] . A few studies, however, reported evidence supporting the opposite conclusion in non-human primates [49][50][51] , various cell types 52,53 and mosquitoes 47 . This discrepancy may reflect the lack of standard panels of ZIKV strains and/or the scarcity of recent African ZIKV strains available from public biobanks and laboratory collections 54 .…”
Section: Introductionmentioning
confidence: 99%